2015
DOI: 10.1186/s13075-015-0778-z
|View full text |Cite
|
Sign up to set email alerts
|

Reanalysis of the Rituximab in ANCA-Associated Vasculitis trial identifies granulocyte subsets as a novel early marker of successful treatment

Abstract: IntroductionIn the present study, we sought to identify markers in patients with anti-neutrophil cytoplasmic antibody (ANCA)-associated vasculitis (AAV) that distinguish those achieving remission at 6 months following rituximab or cyclophosphamide treatment from those for whom treatment failed in the Rituximab in ANCA-Associated Vasculitis (RAVE) trial.MethodsClinical and flow cytometry data from the RAVE trial were downloaded from the Immunology Database and Analysis Portal and Immune Tolerance Network TrialS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 24 publications
0
18
0
1
Order By: Relevance
“…For instance, data repurposing initiatives from ImmPort (www.immpo rt.org), a data warehouse that includes clinical trial subject-level data from National Institute of Allergy and Infectious Diseases-funded immunology studies, facilitated the translation of new insights into discoveries. 38,39 Using ImmPort public data, Nasrallah et al 40 sought to identify biomarkers for patients with antineutrophil cytoplasmic antibody-associated vasculitis who failed treatment with cyclophosphamide or rituximab therapy. Their secondary analysis of rituximab-treated participants in the Anti-Neutrophil Cytoplasmic Antibodies-Associated Vasculitis RAVE trial revealed distinct subsets of granulocytes at baseline in patients with vasculitis who achieved a complete remission with cyclophosphamide or rituximab treatment compared with patients who failed to achieve remission.…”
Section: Drug Development Toolsmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, data repurposing initiatives from ImmPort (www.immpo rt.org), a data warehouse that includes clinical trial subject-level data from National Institute of Allergy and Infectious Diseases-funded immunology studies, facilitated the translation of new insights into discoveries. 38,39 Using ImmPort public data, Nasrallah et al 40 sought to identify biomarkers for patients with antineutrophil cytoplasmic antibody-associated vasculitis who failed treatment with cyclophosphamide or rituximab therapy. Their secondary analysis of rituximab-treated participants in the Anti-Neutrophil Cytoplasmic Antibodies-Associated Vasculitis RAVE trial revealed distinct subsets of granulocytes at baseline in patients with vasculitis who achieved a complete remission with cyclophosphamide or rituximab treatment compared with patients who failed to achieve remission.…”
Section: Drug Development Toolsmentioning
confidence: 99%
“…Hence, this study suggested that profiling patients based on cell-based markers might help to make therapeutic decisions and inform future trial designs. 40 Another example of data repurposing includes the assessment of the post-donation conditions for living donors in solid organ transplantation included in the ImmPort database. A curated data set, immTransplant, with postdonation outcomes for kidney living donors were derived from 20 clinical studies (clinical trials and observational studies) in ImmPort.…”
Section: Drug Development Toolsmentioning
confidence: 99%
“…Subgruppenanalysen der RAVE-Studie konnten ein besseres Ansprechen von RTX im Vergleich zu CYC bei Patienten mit Rezidiv und bei PR3-ANCA positiven Patienten demonstrierten [3,4]. Eine Posthoc-Analyse der RAVE-Studie identifizierte außerdem einen niedrigen "Granularity-Index" weißer Blutkörperchen als einen Indikator für das bessere Ansprechen auf CYC im Vergleich zu RTX [5]. Alle diese Subgruppen-bzw.…”
Section: Remissionsinduktion Bei Granulomatose Mit Polyangiitis (Gpa)unclassified
“…Such raw data can be re-analyzed to defend the reproducibility of statistical testing from the original publication, and the aggregation of multiple studies through meta-analysis can be used to increase power to detect subtle signals. They could also be useful for new scientific discoveries, such as finding patient subsets that best respond to an intervention [76], or predicting why drugs might be succeeding or failing in clinical trials.…”
Section: Integrating Modeling and Experimentation For 21st Century Immentioning
confidence: 99%